METAL CONTENTS IN RAWAL LAKE WATER AND FISH - Mashiatullah, A.; Chaudhary, M. Z.; Javed, T.; Khan, E. U. (The Nucleus, 2020)
Concentration of metals (Al, Fe, Mn, As, Sr, Zn, Cd, Cr, Cu, Pb, Ni, and Co) were measured in Rawal lake water and fish. The objective of the study was to determine metal load in Rawal lake water and fish. Physiochemical characteristics of the lake water were also determined. Rawal lake was monitored at 12 sites in three profiles. At each station, water samples were collected from surface, middle and bottom column. Results of the study revealed that water quality of Rawal Lake, in terms of physiochemical characteristics (pH, electrical conductivity, total dissolved solids and alkalinity), is satisfactory and the values of these parameters are within permissible water quality limits. Metal concentrations at different stations varied widely because these are carried into the lake from different sources. However, in lake water, average As is found in high concentration while average contents of Al, Fe, Mn, Sr and Zn were within WHO permissible limits. Ni, Cd, Cr, Cu, Co and Pb were below detection limit (< 0.001 Î¼g/ml). In general, metal ions concentration increased with water column depth which indicates that metal ions originated from weathering. Metal ions in two species of fish (Labeo rohita and Tor species) were higher than the levels found in water. The study concludes that increasing population in catchments Zone of Rawal Lake must be regularized and there should be some management policy to check further increase in the number of poultry and agro farms in the catchments zones.